2021
DOI: 10.1155/2021/5527736
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E Gene Polymorphism with Lipid Profile and Ischemic Stroke Risk in Type 2 Diabetes Mellitus Patients

Abstract: Background. Altered lipid profiles have consistently been linked to cerebrovascular events. Ischemic stroke (IS) was a common comorbid condition established in type 2 diabetes mellitus (T2DM). The apolipoprotein E (ApoE) gene which has a notably critical function in lipoprotein metabolism is believed as one of the potential candidate genes susceptible to IS complications in T2DM. This research aimed to determine the association of apolipoprotein E gene polymorphism with lipid profile and IS risk in T2DM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In agreement with these results, Al-Shammari et al (31) reported no association between APOE allelic patterns and the blood lipid levels in healthy Kuwaiti Arab subjects and patients with combined hyperlipidemia. A recent study conducted in 2021 on Indonesian T2D patients reported no association between TC, TG, and LDL-C levels with APOE polymorphisms, but showed that ε2 and ε4 carriers had lower levels of HDL-C (32). Other studies revealed that APOE polymorphisms were associated with serum lipid levels in healthy controls but not in T2D patients (33,34).…”
Section: Discussionmentioning
confidence: 97%
“…In agreement with these results, Al-Shammari et al (31) reported no association between APOE allelic patterns and the blood lipid levels in healthy Kuwaiti Arab subjects and patients with combined hyperlipidemia. A recent study conducted in 2021 on Indonesian T2D patients reported no association between TC, TG, and LDL-C levels with APOE polymorphisms, but showed that ε2 and ε4 carriers had lower levels of HDL-C (32). Other studies revealed that APOE polymorphisms were associated with serum lipid levels in healthy controls but not in T2D patients (33,34).…”
Section: Discussionmentioning
confidence: 97%
“…The accuracy of the data mining methods with neural network approaches has kept getting better in studies on diabetes. In [21], the research scientists address data standardization, asymmetry, and pattern enhancement, respectively, using an adaptive variational with sparse coders and standard uniformity. After that, perceptron was employed to classify data with 93.5% accuracy.…”
Section: IImentioning
confidence: 99%